The reduction of CSF tumor necrosis factor alpha levels in schizophrenia: no correlations with psychopathology and coincident metabolic characteristics - Zhu H; Wang D; Liu X (Neuropsychiatric Disease and Treatment, 2016)
Haibing Zhu,1 Danfeng Wang,2 Xiuqin Liu3 1Department of Psychiatry, Panyu Central Hospital, 2Department of Psychiatry, Guangzhou Psychiatric Hospital, 3Department of Nuclear Medicine, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China Aim: The aim of this study was to assess whether tumor necrosis factor alpha (TNF-α) levels are correlated with the behavioral syndrome of schizophrenia and/or metabolic abnormalities. Methods: Sixty patients with first-onset schizophrenia were recruited. The concentrations of TNF-α in the cerebrospinal fluid (CSF) were determined in 22 schizophrenia patients and ten patients with nonsuppurative appendicitis using a radioimmunoassay. Physiological characteristics such as fasting blood glucose, fasting insulin, triglycerides, corrected QT interval, waist circumference, and body mass index were measured prior to CSF collection. Subjects were screened for insulin resistance using the homeostasis model assessment. The extent of positive and negative behavioral symptoms was scored using the Positive and Negative Syndrome Scale. Results: The CSF TNF-α levels in schizophrenic patients were significantly lower than those in the control group. The age of disease onset was positively correlated with the CSF TNF-α level using Pearson correlation analysis (r=0.37, P<0.05). There were no significant differences in CSF TNF-α levels in terms of age, duration of schizophrenia, or systolic and diastolic blood pressure. Furthermore, the CSF TNF-α levels were not significantly correlated with fasting blood glucose, fasting insulin, insulin resistance index, triglycerides, corrected QT interval, waist circumference, or body mass index. No significant correlation was found between CSF TNF-α levels and the Positive and Negative Syndrome Scale total scores or other factors scores. There were also no significant differences in CSF TNF-α levels between patients with schizophrenia types I and II. Conclusion: CSF TNF-α levels are decreased in schizophrenia, although this reduction does not correlate with the psychopathology or coincident metabolic characteristics of this disease. Keywords: schizophrenia, tumor necrosis factor alpha, cerebrospinal fluid, psychopathology, metabolic abnormalities